2015
DOI: 10.1097/icl.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nepafenac Eye Drops on Pain Associated With Pterygium Surgery

Abstract: Treatment with nepafenac ophthalmic suspension 0.1% significantly reduced postoperative pain compared with placebo after pterygium surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[57][58][59][60] Pain Control Bhikoo et al 61 supported the use of 2 mL of intraoperative subtenon bupivacaine 0.5% toward the end of surgery to improve postoperative comfort by reducing pain and irritation. Ozcimen et al 62 determined that the use of topical nepafenac 0.1% every 8 hours for 3 days postoperatively significantly reduces postoper-ative pain. Goktas et al 63 suggests topical cyclopentolate 1% 3 times daily for 3 days postoperatively in addition to artificial tears also significantly lowers postoperative pain in comparison with artificial tears alone.…”
Section: Bandage Contact Lens Versus Patchingmentioning
confidence: 99%
“…[57][58][59][60] Pain Control Bhikoo et al 61 supported the use of 2 mL of intraoperative subtenon bupivacaine 0.5% toward the end of surgery to improve postoperative comfort by reducing pain and irritation. Ozcimen et al 62 determined that the use of topical nepafenac 0.1% every 8 hours for 3 days postoperatively significantly reduces postoper-ative pain. Goktas et al 63 suggests topical cyclopentolate 1% 3 times daily for 3 days postoperatively in addition to artificial tears also significantly lowers postoperative pain in comparison with artificial tears alone.…”
Section: Bandage Contact Lens Versus Patchingmentioning
confidence: 99%
“…It has been observed that nepafenac 0.1% eye drops administered thrice a day for 3 days (in association with postoperative therapy with topical ciprofloxacin, fluorometholone, and artificial tears) provided a significant pain reduction when compared with placebo after pterygium excision with autologous conjunctival graft. 166 An alternative treatment for rapid corneal epithelial healing and pain reduction after pterygium surgery is represented by autologous serum eye drops, which led to favorable results, as reported in a study by Sul et al 167 However, the evidence of autologous serum eye drops in pterygium surgery is currently limited. In addition, systemic analgesic drugs should be considered in the management of postoperative pain, especially if intense or persistent despite adequate topical treatment.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…2014), ocular discomfort after vitreous injections (Ulrich 2014) and postoperative pain associated with pterygium surgery (Ozcimen et al. 2015). However, we did not find published studies describing the frequency of nepafenac use or dispensing for the approved indication or other conditions in routine health care, as we did in this study.…”
Section: Discussionmentioning
confidence: 99%